How energy consumption, industrial growth, urbanization, and CO2 emissions affect economic growth in Pakistan? A novel dynamic ARDL simulations approach. (15th April 2021) - Abbasi, Kashif Raza; Shahbaz, Muhammad; Jiao, Zhilun; Tufail, Muhammad
Abstract: Pakistan has been confronting economic challenges for two decades due to many factors such as the electricity crisis, among others. It is therefore essential to identify such factors that may play a constructive role in economic growth. In doing so, this study investigates the determinants of economic growth in Pakistan from 1972 to 2018. The dynamic autoregressive distributed lag (ARDL) simulations approach is applied to analyze positive and negative changes in energy consumption, industrial growth, urbanization, and carbon emissions on economic growth in Pakistan. The frequency-domain causality (FDC) test is utilized to check long-, medium-, and short-run relationships. Our empirical evidence reveals that electricity consumption and industrial value-added have a short- and long-run impact on economic growth. However, carbon emissions and urbanization have positive effects on economic growth in the short run. Consequently, we conclude that energy consumption, industrial growth, urbanization, and CO2 emissions positively impact economic growth in Pakistan. The FDC also confirms the long-, medium-, and short-run causality hypothesis. The study suggests a requirement to integrate better electricity generation and management with the planning of economic policies. The government is advised to invest more in renewable energy to protect the environment from degradation, ban the import of low-efficiency electrical appliances, and evaluate the refugee reception policy. Highlights: The study examines the determinants of economic growth in Pakistan from 1972 to 2018. This study employs a newly developed, dynamic ARDL simulation model. The study also applied the frequency-domain causality (FDC) test. Empirical results show long and short-run significant impacts on economic growth. However, the FDC evidence revealed the short, medium, and long-run relationship.